Janela - Cardoso, Luiza Meneghetti; Soares, Bianca Eduarda Ladislau; Souza, Helena Engelbrecht de; Sulato, Beatriz de Campos; Orlandini, Giovanna Camillo (Universidade Federal de São Carlos, 2021)
Gabi and Simone are quarantined at home during the 2020 pandemic in Brazil. When comparing their routines side by side, we notice the similarities that confinement imposes on both characters
Window
Keywords: Pandemia; Pandemic; Live-action; Curta-metragem; Short film; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::COMUNICACAO VISUAL